The colony count of Escherichia coli in the stool of palmar arsenical keratosis following probiotics supplementation (Bangladesh Journal of Pharmacology, 2014)
The role of probiotics supplementation for 12 weeks on the colony count of Escherichia coli in the stool of moderate palmar arsenical keratosis (14), arsenic exposed controls (15) and healthy volunteers (9) were studied. The mean colony counts of E. coli in the stool of arsenic exposed controls and patients were reduced to 7.3 x 1011 CFU/g and 3.2 x 1011 CFU/g respectively in comparison to healthy volunteers (11.1 x 1011 CFU/g). After probiotics supplementation, the E. coli count was significantly increased in patients (p=0.000) and arsenic exposed controls (p=0.000) in comparison to healthy volunteers (p=0.027). Patients excreted less arsenic through stool and supplementation with probiotics showed increased excretion of arsenic only in patients  The level of arsenic in nail of patients was more than the arsenic exposed controls and healthy controls. Probiotics supplementation did not show any significant change. This study suggests that arsenicosis reduced the stool colony count of E. coli, less excretion of arsenic and probiotics supplementation reversed the processes.